Characterization and taxonomic key for tadpoles (Amphibia: Anura) from the northwestern region of São Paulo State, Brazil - Rossa-feres, Denise De Cerqueira [UNESP]; Nomura, Fausto [UNESP] (Instituto Virtual da Biodiversidade | BIOTA - FAPESP, 2006)
Difficulties in species identification and the absence of taxonomic keys are several of the obstacles in elaborating adequate conservation, management and habitat recovery programs. This study provides a taxonomic key, morphological characterization, and drawings for the 22 known anuran tadpoles from the northwestern region of São Paulo state, southeastern Brazil. Specimens of all species analyzed are deposited in the scientific amphibian collection of Universidade Estadual Paulista (DZSJRP), São José do Rio Preto, SP.

Dificuldades na identificação de espécies e a ausência de chaves taxonômicas são alguns dos maiores obstáculos na elaboração de programas de conservação, manejo e recuperação de hábitats. Este estudo apresenta uma chave taxonômica, caracterização morfológica e desenhos para as 22 espécies de larvas de anuros conhecidas para a região noroeste do Estado de São Paulo, sudeste do Brasil. Espécimes de todos os girinos analisados estão depositados na coleção científica da Universidade Estadual Paulista, São José do Rio Preto, SP (DZSJRP).
Caracterização e chave taxonômica para girinos (Amphibia: Anura) da região noroeste do estado de São Paulo, Brasil
Keywords: Cerrado; Neotropical region; biodiversity; morphological variation; taxonomy; Cerrado; região neotropical; biodiversidade; variação morfológica; taxonomia